Curbing antimicrobial resistance in post-COVID Africa: Challenges, actions and recommendations - Shomuyiwa D.O. (2023)
Background: Antimicrobial self-medication and use have significantly increased in the COVID-19 era—increasing antibiotic consumption and resulting in a high prevalence of antimicrobial resistance in Africa (AMR). We conducted a narrative review to investigate challenges associated with curbing AMR in a post-COVID-19 setting in Africa, suggesting practical measures applicable for policy-informed implementation. Method: A narrative review was performed to pinpoint AMR challenges and actions on the African continent. A comprehensive search was conducted in the scientific databases that include PubMed, PubMed Central and Google Scholar using predetermined search terms. Results: The emergence of the COVID-19 outbreak has added to the challenges of tackling AMR on the continent, which has jeopardized AMR interventions' hard-won gains. Identified challenges have been Health systems disruption, Irrational Antimicrobial Use, Weak Antimicrobials Regulatory Ecosystem, Inefficient Population Infection Prevention, and Control Practices, Inadequate access to Health Services and data challenge on AMR surveillance. Conclusion: The COVID-19 pandemic fueled AMR in Africa. There is a need for AMR control post-COVID, such as measures for ongoing antimicrobial stewardship and good infection control practices. Further, curbing AMR requires rigorous regulatory enforcement and efficient AMR Surveillance. There should be a body to raise AMR awareness among the population. Research, Innovation and Technology could play an essential role supported by capacity building and global partnership.